Decentralization, participation and deliberation in water governance: a case study of the implications for Guarulhos, Brazil. (October 2014) - van den Brandeler, Francine; Hordijk, Michaela; von Schönfeld, Kim; Sydenstricker-Neto, John
After the return to democracy in the late 1980s, Brazil developed a new system of water governance with a decentralization of responsibilities and the formation of participatory, deliberative institutions that characterized the governance reforms in general. Tripartite "water basin committees", with an equal representation of state, municipal and civil society actors, are now responsible for water resource management in each basin and for decisions that affect urban water governance. However, state representatives come from entities established long before the reforms, raising the question of whether the new participatory bodies can change water management practices. This paper suggests that despite the process of transition in water governance, the underlying power inequalities have not been addressed and major decisions are still being taken outside the new deliberative bodies. Technocratic government actors maintain a claim on authority through their economic superiority and their use of expert knowledge, ultimately inhibiting the influence of other actors.